A genomic strategy for precision medicine in rare diseases: integrating customized algorithms into clinical practice. - Méndez-Vidal, Cristina; Bravo-Gil, Nereida; Perez-Florido, Javier; Marcos-Luque, Irene; Fernández, Raquel M; Fernandez-Rueda, Jose Luis; González-del Pozo, María; Martín-Sánchez, Marta; Fernández-Suárez, Elena; Mena, Marcela; Carmona, Rosario; Dopazo, Joaquin; et al. (J Transl Med, 2025)
BACKGROUND: Despite the use of Next-Generation Sequencing (NGS) as the gold standard for the diagnosis of rare diseases, its clinical implementation has been challenging, limiting the cost-effectiveness of NGS and the understanding, control and safety essential for decision-making in clinical applications. Here, we describe a personalized NGS-based strategy integrating precision medicine into a public healthcare system and its implementation in the routine diagnosis process during a five-year pilot program. METHODS: Our approach involved customized probe designs, the generation of virtual panels and the development of a personalized medicine module (PMM) for variant prioritization. This strategy was applied to 6500 individuals including 6267 index patients and 233 NGS-based carrier screenings. RESULTS: Causative variants were identified in 2061 index patients (average 32.9%, ranging from 12 to 62% by condition). Also, 131 autosomal-recessive cases could be partially genetically diagnosed. These results led to over 5000 additional studies including carrier, prenatal and preimplantational tests or pharmacological and gene therapy treatments. CONCLUSION: This strategy has shown promising improvements in the diagnostic rate, facilitating timely diagnosis and gradually expanding our services portfolio for rare diseases. The steps taken towards the integration of clinical and genomic data are opening new possibilities for conducting both retrospective and prospective healthcare studies. Overall, this study represents a major milestone in the ongoing efforts to improve our understanding and clinical management of rare diseases, a crucial area of medical research and care.
Keywords: Algorithms; Female; Genomics; High-Throughput Nucleotide Sequencing; Humans; Precision Medicine; rare diseases

CSVS, a crowdsourcing database of the Spanish population genetic variability. - Peña-Chilet, Maria; Roldán, Gema; Perez-Florido, Javier; Ortuno, Francisco M; Carmona, Rosario; Aquino, Virginia; López-López, Daniel; Loucera, Carlos; Fernandez-Rueda, Jose L; Gallego, Asunción; Garcia-Garcia, Francisco; González-Neira, Anna; et al. (Nucleic Acids Res, 2021)
The knowledge of the genetic variability of the local population is of utmost importance in personalized medicine and has been revealed as a critical factor for the discovery of new disease variants. Here, we present the Collaborative Spanish Variability Server (CSVS), which currently contains more than 2000 genomes and exomes of unrelated Spanish individuals. This database has been generated in a collaborative crowdsourcing effort collecting sequencing data produced by local genomic projects and for other purposes. Sequences have been grouped by ICD10 upper categories. A web interface allows querying the database removing one or more ICD10 categories. In this way, aggregated counts of allele frequencies of the pseudo-control Spanish population can be obtained for diseases belonging to the category removed. Interestingly, in addition to pseudo-control studies, some population studies can be made, as, for example, prevalence of pharmacogenomic variants, etc. In addition, this genomic data has been used to define the first Spanish Genome Reference Panel (SGRP1.0) for imputation. This is the first local repository of variability entirely produced by a crowdsourcing effort and constitutes an example for future initiatives to characterize local variability worldwide. CSVS is also part of the GA4GH Beacon network. CSVS can be accessed at: http://csvs.babelomics.org/.
Keywords: Alleles; Chromosome Mapping; Crowdsourcing; Databases, Genetic; Exome; Gene Frequency; Genetic Variation; Genetics, Population; Genome, Human; Genomics; Humans; Internet; Precision Medicine; Software; Spain

Improving the management of Inherited Retinal Dystrophies by targeted sequencing of a population-specific gene panel. - Bravo-Gil, Nereida; Méndez-Vidal, Cristina; Romero-Pérez, Laura; González-del Pozo, María; Rodríguez-de la Rúa, Enrique; Dopazo, Joaquin; Borrego, Salud; Antiňolo, Guillermo (Sci Rep, 2016)
Next-generation sequencing (NGS) has overcome important limitations to the molecular diagnosis of Inherited Retinal Dystrophies (IRD) such as the high clinical and genetic heterogeneity and the overlapping phenotypes. The purpose of this study was the identification of the genetic defect in 32 Spanish families with different forms of IRD. With that aim, we implemented a custom NGS panel comprising 64 IRD-associated genes in our population, and three disease-associated intronic regions. A total of 37 pathogenic mutations (14 novels) were found in 73% of IRD patients ranging from 50% for autosomal dominant cases, 75% for syndromic cases, 83% for autosomal recessive cases, and 100% for X-linked cases. Additionally, unexpected phenotype-genotype correlations were found in 6 probands, which led to the refinement of their clinical diagnoses. Furthermore, intra- and interfamilial phenotypic variability was observed in two cases. Moreover, two cases unsuccessfully analysed by exome sequencing were resolved by applying this panel. Our results demonstrate that this hypothesis-free approach based on frequently mutated, population-specific loci is highly cost-efficient for the routine diagnosis of this heterogeneous condition and allows the unbiased analysis of a miscellaneous cohort. The molecular information found here has aid clinical diagnosis and has improved genetic counselling and patient management.
Keywords: Alleles; Computer Simulation; DNA Copy Number Variations; DNA Mutational Analysis; Eye Proteins; Gene Library; Genetic Association Studies; Genetic Heterogeneity; Genetic Therapy; High-Throughput Nucleotide Sequencing; Humans; mutation; Phenotype; Retinal Dystrophies

Re-evaluation casts doubt on the pathogenicity of homozygous USH2A p.C759F. - Pozo, María González-Del; Bravo-Gil, Nereida; Méndez-Vidal, Cristina; Montero-de-Espinosa, Ignacio; Millán, José M; Dopazo, Joaquin; Borrego, Salud; Antiňolo, Guillermo (Am J Med Genet A, 2015)
Mutations in USH2A are a common cause of Retinitis Pigmentosa (RP). Among the most frequently reported USH2A variants, c.2276G>T (p.C759F) has been found in both affected and healthy individuals. The pathogenicity of this variant remains controversial since it was detected in homozygosity in two healthy siblings of a Spanish family (S23), eleven years ago. The fact that these individuals remain asymptomatic today, prompted us to study the presence of other pathogenic variants in this family using targeted resequencing of 26 retinal genes in one of the affected individuals. This approach allowed us to identify one novel pathogenic homozygous mutation in exon 13 of PDE6B (c.1678C>T; p.R560C). This variant cosegregated with the disease and was absent in 200 control individuals. Remarkably, the identified variant in PDE6B corresponds to the mutation responsible of the retinal degeneration in the naturally occurring rd10 mutant mice. To our knowledge, this is the first report of the identification of the rd10 mice mutation in a RP family. These findings, together with a review of the literature, support the hypothesis that homozygous p.C759F mutations are not pathogenic and led us to exclude the implication of p.C759F in the RP of family S23. Our results indicate the need of re-evaluating all families genetically diagnosed with this mutation.
Keywords: Base Sequence; Cyclic Nucleotide Phosphodiesterases, Type 6; Extracellular Matrix Proteins; Gene Library; Humans; Molecular Sequence Data; Mutation, Missense; Pedigree; Retinitis pigmentosa; Sequence Analysis, DNA; Spain

Exome sequencing reveals novel and recurrent mutations with clinical significance in inherited retinal dystrophies. - González-del Pozo, María; Méndez-Vidal, Cristina; Bravo-Gil, Nereida; Vela-Boza, Alicia; Dopazo, Joaquin; Borrego, Salud; Antiňolo, Guillermo (PLoS One, 2014)
This study aimed to identify the underlying molecular genetic cause in four Spanish families clinically diagnosed of Retinitis Pigmentosa (RP), comprising one autosomal dominant RP (adRP), two autosomal recessive RP (arRP) and one with two possible modes of inheritance: arRP or X-Linked RP (XLRP). We performed whole exome sequencing (WES) using NimbleGen SeqCap EZ Exome V3 sample preparation kit and SOLID 5500xl platform. All variants passing filter criteria were validated by Sanger sequencing to confirm familial segregation and the absence in local control population. This strategy allowed the detection of: (i) one novel heterozygous splice-site deletion in RHO, c.937-2_944del, (ii) one rare homozygous mutation in C2orf71, c.1795T>C; p.Cys599Arg, not previously associated with the disease, (iii) two heterozygous null mutations in ABCA4, c.2041C>T; p.R681* and c.6088C>T; p.R2030*, and (iv) one mutation, c.2405-2406delAG; p.Glu802Glyfs*31 in the ORF15 of RPGR. The molecular findings for RHO and C2orf71 confirmed the initial diagnosis of adRP and arRP, respectively, while patients with the two ABCA4 mutations, both previously associated with Stargardt disease, presented symptoms of RP with early macular involvement. Finally, the X-Linked inheritance was confirmed for the family with the RPGR mutation. This latter finding allowed the inclusion of carrier sisters in our preimplantational genetic diagnosis program.
Keywords: Adolescent; Adult; Amino Acid Sequence; Base Sequence; Child; Chromosome Segregation; DNA Mutational Analysis; Exome; Family; Female; Humans; Inheritance Patterns; Male; Middle Aged; Molecular Sequence Data; mutation; Pedigree; Retinal Dystrophies; Rhodopsin

Novel RP1 mutations and a recurrent BBS1 variant explain the co-existence of two distinct retinal phenotypes in the same pedigree. - Méndez-Vidal, Cristina; Bravo-Gil, Nereida; González-del Pozo, María; Vela-Boza, Alicia; Dopazo, Joaquin; Borrego, Salud; Antiňolo, Guillermo (BMC Genet, 2014)
BACKGROUND: Molecular diagnosis of Inherited Retinal Dystrophies (IRD) has long been challenging due to the extensive clinical and genetic heterogeneity present in this group of disorders. Here, we describe the clinical application of an integrated next-generation sequencing approach to determine the underlying genetic defects in a Spanish family with a provisional clinical diagnosis of autosomal recessive Retinitis Pigmentosa (arRP). RESULTS: Exome sequencing of the index patient resulted in the identification of the homozygous BBS1 p.M390R mutation. Sanger sequencing of additional members of the family showed lack of co-segregation of the p.M390R variant in some individuals. Clinical reanalysis indicated co-ocurrence of two different phenotypes in the same family: Bardet-Biedl syndrome in the individual harboring the BBS1 mutation and non-syndromic arRP in extended family members. To identify possible causative mutations underlying arRP, we conducted disease-targeted gene sequencing using a panel of 26 IRD genes. The in-house custom panel was validated using 18 DNA samples known to harbor mutations in relevant genes. All variants were redetected, indicating a high mutation detection rate. This approach allowed the identification of two novel heterozygous null mutations in RP1 (c.4582_4585delATCA; p.I1528Vfs*10 and c.5962dupA; p.I1988Nfs*3) which co-segregated with the disease in arRP patients. Additionally, a mutational screening in 96 patients of our cohort with genetically unresolved IRD revealed the presence of the c.5962dupA mutation in one unrelated family. CONCLUSIONS: The combination of molecular findings for RP1 and BBS1 genes through exome and gene panel sequencing enabled us to explain the co-existence of two different retinal phenotypes in a family. The identification of two novel variants in RP1 suggests that the use of panels containing the prevalent genes of a particular population, together with an optimized data analysis pipeline, is an efficient and cost-effective approach that can be reliably implemented into the routine diagnostic process of diverse inherited retinal disorders. Moreover, the identification of these novel variants in two unrelated families supports the relatively high prevalence of RP1 mutations in Spanish population and the role of private mutations for commonly mutated genes, while extending the mutational spectrum of RP1.
Keywords: Bardet-Biedl Syndrome; Base Sequence; Case-Control Studies; DNA Mutational Analysis; Eye Proteins; Genes, Recessive; Genetic Association Studies; Humans; Microsatellite Repeats; Microtubule-Associated Proteins; Mutation, Missense; Pedigree; Phenotype; Retina; Retinitis pigmentosa

Pathways systematically associated to Hirschsprung's disease. - Fernández, Raquel M; Bleda, Marta; Luzón-Toro, Berta; García-Alonso, Luz; Arnold, Stacey; Sribudiani, Yunia; Besmond, Claude; Lantieri, Francesca; Doan, Betty; Ceccherini, Isabella; Lyonnet, Stanislas; Hofstra, Robert Mw; et al. (Orphanet J Rare Dis, 2013)
Despite it has been reported that several loci are involved in Hirschsprung's disease, the molecular basis of the disease remains yet essentially unknown. The study of collective properties of modules of functionally-related genes provides an efficient and sensitive statistical framework that can overcome sample size limitations in the study of rare diseases. Here, we present the extension of a previous study of a Spanish series of HSCR trios to an international cohort of 162 HSCR trios to validate the generality of the underlying functional basis of the Hirschsprung's disease mechanisms previously found. The Pathway-Based Analysis (PBA) confirms a strong association of gene ontology (GO) modules related to signal transduction and its regulation, enteric nervous system (ENS) formation and other processes related to the disease. In addition, network analysis recovers sub-networks significantly associated to the disease, which contain genes related to the same functionalities, thus providing an independent validation of these findings. The functional profiles of association obtained for patients populations from different countries were compared to each other. While gene associations were different at each series, the main functional associations were identical in all the five populations. These observations would also explain the reported low reproducibility of associations of individual disease genes across populations.
Keywords: Female; Genetic Predisposition to Disease; Genotype; Hirschsprung Disease; Humans; Male; Polymorphism, Single Nucleotide

Four new loci associations discovered by pathway-based and network analyses of the genome-wide variability profile of Hirschsprung's disease. - Fernández, Raquel Ma; Bleda, Marta; Núñez-Torres, Rocío; Medina, Ignacio; Luzón-Toro, Berta; García-Alonso, Luz; Torroglosa, Ana; Marbà, Martina; Enguix-Riego, Ma Valle; Montaner, David; Antiňolo, Guillermo; Dopazo, Joaquin; et al. (Orphanet J Rare Dis, 2012)
Finding gene associations in rare diseases is frequently hampered by the reduced numbers of patients accessible. Conventional gene-based association tests rely on the availability of large cohorts, which constitutes a serious limitation for its application in this scenario. To overcome this problem we have used here a combined strategy in which a pathway-based analysis (PBA) has been initially conducted to prioritize candidate genes in a Spanish cohort of 53 trios of short-segment Hirschsprung's disease. Candidate genes have been further validated in an independent population of 106 trios. The study revealed a strong association of 11 gene ontology (GO) modules related to signal transduction and its regulation, enteric nervous system (ENS) formation and other HSCR-related processes. Among the preselected candidates, a total of 4 loci, RASGEF1A, IQGAP2, DLC1 and CHRNA7, related to signal transduction and migration processes, were found to be significantly associated to HSCR. Network analysis also confirms their involvement in the network of already known disease genes. This approach, based on the study of functionally-related gene sets, requires of lower sample sizes and opens new opportunities for the study of rare diseases.
Keywords: Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Hirschsprung Disease; Humans; Male

Mutation screening of multiple genes in Spanish patients with autosomal recessive retinitis pigmentosa by targeted resequencing. - González-del Pozo, María; Borrego, Salud; Barragán, Isabel; Pieras, Juan I; Santoyo, Javier; Matamala, Nerea; Naranjo, Belén; Dopazo, Joaquin; Antiňolo, Guillermo (PLoS One, 2011)
Retinitis Pigmentosa (RP) is a heterogeneous group of inherited retinal dystrophies characterised ultimately by the loss of photoreceptor cells. RP is the leading cause of visual loss in individuals younger than 60 years, with a prevalence of about 1 in 4000. The molecular genetic diagnosis of autosomal recessive RP (arRP) is challenging due to the large genetic and clinical heterogeneity. Traditional methods for sequencing arRP genes are often laborious and not easily available and a screening technique that enables the rapid detection of the genetic cause would be very helpful in the clinical practice. The goal of this study was to develop and apply microarray-based resequencing technology capable of detecting both known and novel mutations on a single high-throughput platform. Hence, the coding regions and exon/intron boundaries of 16 arRP genes were resequenced using microarrays in 102 Spanish patients with clinical diagnosis of arRP. All the detected variations were confirmed by direct sequencing and potential pathogenicity was assessed by functional predictions and frequency in controls. For validation purposes 4 positive controls for variants consisting of previously identified changes were hybridized on the array. As a result of the screening, we detected 44 variants, of which 15 are very likely pathogenic detected in 14 arRP families (14%). Finally, the design of this array can easily be transformed in an equivalent diagnostic system based on targeted enrichment followed by next generation sequencing.
Keywords: Alleles; DNA Mutational Analysis; Exons; Genetic Variation; Genome; Hispanic or Latino; Humans; Introns; Language; mutation; Mutation, Missense; Oligonucleotide Array Sequence Analysis; Polymerase Chain Reaction; Reproducibility of Results; Retinitis pigmentosa; United States

Mutation spectrum of EYS in Spanish patients with autosomal recessive retinitis pigmentosa. - Barragán, Isabel; Borrego, Salud; Pieras, Juan Ignacio; González-del Pozo, María; Santoyo, Javier; Ayuso, Carmen; Baiget, Montserrat; Millán, José M; Mena, Marcela; Abd El-Aziz, Mai M; Audo, Isabelle; Zeitz, Christina; et al. (Hum Mutat, 2010)
Retinitis pigmentosa (RP) is a heterogeneous group of inherited retinal dystrophies characterised ultimately by the loss of photoreceptor cells. We have recently identified a new gene(EYS) encoding an ortholog of Drosophila space maker (spam) as a commonly mutated gene in autosomal recessive RP. In the present study, we report the identification of 73 sequence variations in EYS, of which 28 are novel. Of these, 42.9% (12/28) are very likely pathogenic, 17.9% (5/28)are possibly pathogenic, whereas 39.3% (11/28) are SNPs. In addition, we have detected 3 pathogenic changes previously reported in other populations. We are also presenting the characterisation of EYS homologues in different species, and a detailed analysis of the EYS domains, with the identification of an interesting novel feature: a putative coiled-coil domain.Majority of the mutations in the arRP patients have been found within the domain structures of EYS. The minimum observed prevalence of distinct EYS mutations in our group of patients is of 15.9% (15/94), confirming a major involvement of EYS in the pathogenesis of arRP in the Spanish population. Along with the detection of three recurrent mutations in Caucasian population, our hypothesis of EYS being the first prevalent gene in arRP has been reinforced in the present study.
Keywords: Amino Acid Sequence; Animals; Case-Control Studies; DNA Mutational Analysis; Drosophila Proteins; Evolution, Molecular; Eye Proteins; Female; Genes, Recessive; Genetic Variation; Humans; Male; Molecular Sequence Data; mutation; Pedigree; Polymorphism, Single Nucleotide; Protein Structure, Tertiary; Retinitis pigmentosa; Spain; Structural Homology, Protein